Measurement Of Absorption Spectra (Optical Density D) - Madaliev Akmaljon Makhammadzhonovich; Usmonov Muhammadabdullah Kakhramon Ogli (Euro Asian Journal Publishing, 2023)
A number of experimental measuring devices were used for optical, magneto-optical and magnetic measurements of rare-earth orthoaluminates and garnets: (a) Installation for measuring the spectra of the degree of MCPL and luminescence. b) Modified single-beam spectrophotometer with continuous recording of the optical absorption signal.
Keywords: crystal; spectrum; luminescence; absorption